Prediction of success in assisted reproductive technology with the help of morphology of the testis - N. G. Kulchenko (Исследования и практика в медицине, 2018)
In the structure of infertile marriage male factor of infertility occurs in about 40-50%. About 30% of infertile men who have sought medical care have oligozoospermia or azoospermia of unknown etiology. The question of the chances of spermatogenesis recovery and increased probability of sperm extraction in repeated assisted reproductive technology (ART) programs is important for both the doctor and the patient.Purpose. To evaluate the morphological changes of spermatogenic epithelium in patients with male infertility in terms of prognosis of ART success.Patients and methods. 264 men with infertility were examined. The scope of clinical study of all patients included: history, examination, determination of blood hormones, study of ejaculate, karyotype, ultrasound. We performed a biopsy of the testis according to the patient's symptoms. Testicular tissue was subjected to morphological examination.Results. Primary infertility was observed in 172 men (65.2%), secondary — 92 (34.8%). 112 (42.4%) patients had severe infertility. The results of morphological studies in these men showed a different degree of violation of spermatogenesis. Based on the study, a diagnostic algorithm of patients with male infertility is proposed, which allows to predict the success of ART taking into account morphological changes in the testicle.Conclusion. On the basis of clinical and morphological study of the features of spermatogenesis of a particular patient a plan can be made for further personal diagnostic and therapeutic measures.